2003
DOI: 10.1021/jp035198z
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of a Series of Dissymmetric Gemini Surfactants in Aqueous Solution

Abstract: A series of dissymmetric gemini surfactants, [C m H 2m+1 (CH 3 ) 2 N(CH 2 ) 6 N(CH 3 ) 2 C n H 2n+1 ]Br 2 (designated as C m C 6 C n Br 2 , with constant m + n ) 24 and m ) 12, 13, 14, 16, 18), have been investigated by electrical conductivity measurement, steady-state fluorescence measurement, and time-resolved fluorescence quenching. The critical micelle concentration (CMC) and the micelle aggregation number (N) were determined and the micropolarity of micelle was characterized. The micelle ionization degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
85
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 45 publications
14
85
0
1
Order By: Relevance
“…This is not rationalized by the consideration of surfactant geometry on the basis of packing parameter 13 , since rough calculations do not suggest remarkable differences in the overall packing parameter between the two surfactants. We note that Wang and co-workers have reported opposite behaviors 7 . They have studied aqueous solution properties of cationic heterogemini surfactants α-6-β, where α and β represent the hydrocarbon chain lengths under the fixed total carbon number of α β 24 as a function of their dissymmetry i.e., α/β and found the decreased cmc with decreasing symmetry.…”
Section: Molecular Characteristicsmentioning
confidence: 58%
See 2 more Smart Citations
“…This is not rationalized by the consideration of surfactant geometry on the basis of packing parameter 13 , since rough calculations do not suggest remarkable differences in the overall packing parameter between the two surfactants. We note that Wang and co-workers have reported opposite behaviors 7 . They have studied aqueous solution properties of cationic heterogemini surfactants α-6-β, where α and β represent the hydrocarbon chain lengths under the fixed total carbon number of α β 24 as a function of their dissymmetry i.e., α/β and found the decreased cmc with decreasing symmetry.…”
Section: Molecular Characteristicsmentioning
confidence: 58%
“…3.3 Effects of molecular symmetry on the physicochemical properties of aqueous SOH-9,9-Am10 and SOH-12,6-Am10 solutions It has been reported that molecular symmetry of heterogemini surfactants plays a signifi cant role in their aqueous solution properties 7 . In our current work, we have studied this effect using two heterogemini surfactants, SOH-9,9-Am10 and SOH-12,6-Am10.…”
Section: Molecular Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sikirić et al investigated the effect of spacer length on dissymmetric surfactants 12,13 and found that the Krafft temperature increases linearly with spacer length and that both adsorption at the air/water interface and micellization in aqueous solution are heavily dependent on the spacer length. Yan et al synthesized C m C 6 C n Br 2 with m n 24, where m 12, 13, 14, 16, or 18, and found that, as the m/n ratio was increased, the surface activities improved, the CMC values decreased linearly, and the aggregation numbers at the CMC increased slightly 14,15 . These studies investigating dissymmetric surfactants focused on the choice of whether to fix the total carbon numbers of the hydrocarbon chains and their spacers or not.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the degree of dissymmetry, the critical micelle concentration (cmc) decreases linearly, the micelle aggregation number increases slightly, the micelle ionization degree decreases slightly, and so on. Wang et al suggested that the intermolecular and intramolecular interactions between the hydrophobic alkyl chains exist for the symmetric gemini surfactants, while the intramolecular interaction weakens as the degree of dissymmetr y increases 4 ) . Thus, the hydrophobic interaction of dissymmetric gemini surfactants must be different from that of symmetric ones.…”
Section: Introductionmentioning
confidence: 99%